Environmentally Conscious Development, Clean And Healthy Living: A Global Perspective Towards A Healthy And Sustainable Society - Levi Anatolia S.M. Exposto (Public Health and Safety International Journal, 2026)
Environmentally sound development is a global paradigm that places environmental quality as a primary determinant of human health and long-term development sustainability. In the context of increasing anthropogenic pressure on the global ecosystem, the integration of environmental and health dimensions is becoming increasingly essential in the formulation of development policies. This article aims to conduct a comprehensive review of the concept, theoretical basis, implementation strategies, and various challenges in implementing environmentally sound development on a global scale, including its implications for public health and the achievement of the Sustainable Development Goals ( SDGs ). The method used is a semi-systematic literature review with a qualitative-descriptive approach, which analyzes indexed international scientific publications, global organization reports, and policy documents published between 2015 and 2025. The results of the study indicate that an environmentally based development approach contributes significantly to improving ecosystem quality and reducing the burden of disease related to environmental factors, with estimated reductions in morbidity ranging from 30% to 55% in various global intervention contexts. The successful implementation of this approach is heavily influenced by several key factors, namely the integration of environmental health monitoring systems, strengthening cross-sectoral governance, utilizing technological innovation, and active community involvement. Thus, development based on a clean and healthy environment can be seen as a fundamental prerequisite for achieving sustainable global development, while ensuring the health of current and future generations.